Market-Retention in Fitness Centers: Identifying and Ranking the Factors Affecting Customer Retention - MohammadSadegh Ghadiri; Ali Fahiminezhad; Hadi Bagheri; Seyed Mostafa Tayebi (Shahid Bahonar University of Kerman, 2021)
This study was conducted to identify and to rank the factors affecting market retention in fitness centers.14 participants including the customers and managers of fitness centers participated in a semi-structured interview to collect the required data. Sixteen factors were extracted from the interviews and sixteen experts evaluate the relationships among these factors with pairwise comparisons.Based on Interpretive-Structural Modeling, the factors categorized in five levels, i.e. 1) customer relationship quality,customer experience quality, reputation, price, perceived value and satisfaction, 2) Overall servicequality, secondary services and ethical climate, 3) Training type and schedule, location and accessibility and social responsibility, 4) Interior design and equipment, 5) Manager communication and trainer's competencies.  For the sake of customer retention, fitness centers are required to align their decisions with their customer requirements. Ranking the effective factors in this study can provide the fitness centers' managers with a better understanding of the factors affecting customers' decisions.